Long-Term Effectiveness of a Clinician-Assisted Digital Cognitive Behavioral Therapy Intervention for Smoking Cessation: Secondary Outcomes From a Randomized Controlled Trial. Issue 11 (26th April 2022) - Webb, Jamie; Peerbux, Sarrah; Ang, Alfonso; Siddiqui, Sarim; Sherwani, Yusuf; Ahmed, Maroof; MacRae, Hannah; Puri, Hannah; Majeed, Azeem; Glasner, Suzette
Abstract: Introduction: This study evaluated the secondary effectiveness outcomes for Quit Genius, a digital clinician-assisted cognitive behavioral therapy (CBT) intervention for smoking cessation. Methods: Adult smokers ( N = 556) were randomly assigned to Quit Genius ( n = 277), a digital, clinician-assisted CBT intervention or very brief advice (VBA) to stop smoking, an evidence-based, 30-s intervention designed to facilitate quit attempts, coupled with referral to a cessation service ( n = 279). Participants were offered combination nicotine replacement therapy (patches and gum) tailored to individual nicotine dependence. Analyses ( n = 530), by intention-to-treat, compared Quit Genius and VBA at 4, 26, and 52 weeks post-quit date (QD). The primary outcome was self-reported 7-day point prevalence abstinence (PPA) at 4 weeks post-QD. Consecutive 7-day point-prevalence abstinence, defined as abstinent at two or more consecutive timepoints, was examined at weeks 26 and 52 to indicate long-term effectiveness. Abstinence was verified using a random sample of participants with carbon monoxide breath testing of <5 parts per million ( n = 280). Results: Self-reported consecutive 7-day PPA at weeks 26 and 52 for Quit Genius was 27.2% and 22.6%, respectively, compared with VBA which was 16.6% and 13.2% (RR = 1.70, 95% CI, 1.22-2.37; p = .003, 26 weeks; RR = 1.71, 95% CI, 1.17–2.50; P = .005, 52 weeks). Biochemically verified abstinence was significantly different at 26- ( p = .03) but not 52 weeks ( p = .16). Quit Genius participants were more likely to remain abstinent than those who received VBA (RR = 1.71, 95% CI 1.17–2.50; p = .005). Conclusions: This study provides secondary evidence for the long-term effectiveness of Quit Genius in comparison with VBA. Future trials of digital interventions without clinician support and comparisons with active treatment are needed. Implications: The long-term effectiveness of clinician-assisted digital smoking cessation interventions has not been well studied. This study established the long-term effectiveness of an extended CBT-based intervention; results may inform implementation of scalable approaches to smoking cessation in the health system.